Answer:
y = -3/5x - 12/5
Step-by-step explanation:
The equation I'm going to give is going to be in slope-intercept form. If you need it in point-slope, I can do so in an edit or the comments.
Slope-intercept form is: <em>y = mx + b</em> where m is the slope, b is the y-intercept.
So let's plug in our given slope:
y = -3/5x + b
Using this, we now plug in our x- and y-coordinates from the given point to solve for b.
-3 = -3/5(1) + b
-3 = -3/5 + b
Add 3/5 to both sides to isolate variable b.
-3 + 3/5 = b
-15/5 + 3/5 = b
-12/5 = b
Plug this new info back into the original equation and your answer is
y = -3/5x - 12/5
Answer:
c
Step-by-step explanation:
took the test
The mean of the given sample data is 210, and the standard deviation is 7.937.
Given size 'n' = 300
The population proportion 'p' = 0.7
Let 'x' be the random variable of the binomial distribution
a) mean of the binomial distribution = n p = 300 × 0.7
μ = 210
b) variance of the binomial distribution
⇒ n p q
⇒ 300 × 0.7 ×0.3
⇒ σ² = 63
The standard deviation of the binomial distribution:
⇒ √n p q = √63 = 7.937
Thus, the mean of the given sample data is 210, and the standard deviation is 7.937.
Learn more about the standard deviation here:
brainly.com/question/16555520
#SPJ1
The question seems to be incomplete the correct question would be:
describe the sampling of p hat. Assume that the size of the population is 25000 n= 300 p=0.7 a) Determine the mean of the sampling distributionb) Dtermine the standard deviation of the sampling distribution
The slope-intercept form is y = 2x-3.
<u>Step-by-step explanation</u>:
Given,
- The equation of the line is y=2x+7.
- The general equation of the line is in the form y= mx+c.
- where 'm' represents the slope of the line.
<u>Comparing the given equation with general equation, it can be determined that</u> :
m = 2 and c = 7 (y-intercept).
The given line passes through the point (3,3) which is equal to (x1,y1)
Therefore, x1=3 and y1=3.
Substitute m=2 and the values of (x1,y1) in the slope-intercept form,
The slope-intercept form is (y-y1) = m (x-x1)
(y-3) = 2(x-3)
y = 2x-6+3
y = 2x-3